El ms. 880 de la Biblioteca de Montserrat: un breviari romanotoledà del segle XIV - Fossas Colet, Ignasi M. (Miscel·lània litúrgica catalana, 2019)
The library of Montserrat Abbey has a 14th-century Romano-Toledan breviary of unknown provenance registered under the signature Ms. 880. It was first described in 1969 by Revd. Alexandre Olivar, and its importance is due to a large extent to its being the oldest known plenary breviary of the diocese of Toledo. This paper describes the manuscript andoffers a comparative analysis of some of its most representative elements with the aim of presenting the features of this exemplar and the liturgical codification carried out in the Castilian see at that time in history.